Humanity, Communities, Minds, Perceptions and Knowledge on Ice - Bob, Su (Arctic Portal, 2011)
Dr. Bob Su, Department of Water Resources at University of Twente, Netherlands TBC talks here in the NRFP 6th open assembly in Hveragerði, Iceland, in September of 2011. The name of the session is Humanity, Communities, Minds, Perceptions and Knowledge on Ice. Please click on the link above to see the video.